Wybrane elementy racjonalizacji procesu zarządzania zasobami finansowymi miasta - Wartalska, Magdalena; Wasiak, Andrzej (Selected Elements of Management Process of Rationalization of City's Financial Resources, 2005)
Management of commune finances is a complicated and complex process, whose aim is to satisfy collective needs of self-government community in the situation of limited reserves of money. The essential condition for realizing public tasks is effective finance management that affects working efficiency of a commune as a whole and that creates a chance for its harmonious development. The commune, however, is not a self-financing system, which necessitates rationalizing finances in the situation of limited resources (reserves) and realized public tasks. Self-governments and communal administration subordinated to it plays an important part in this process. Communal organs, particularly communal council, make choices (lawfully) regarding concepts of management. If in the commune the management is lead in a modem way, with consideration of the newest tendencies in this field, then the chances given by the surrounding, including financial market, will be used better.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 314-321